A Study of Coupled Creep Damaged Constitutive Model of Artificial Frozen Soil - Dongwei Li; Junhao Chen; Yan Zhou (Advances in Materials Science and Engineering)
Artificial frozen soil is a kind of typical creep material, and the frozen clay under the unloading stress paths of high-confining pressure conforms to the improved the Zienkiewicz–Pande parabola-type yield criterion, and the Mohr–Coulomb yield function can describe the shear yield surface of artificial frozen clay under low-confining pressure. Based on the results of triaxial creep and shear tests for artificial frozen soil, the viscoplastic damage variable and evolution rule of artificial frozen clay were obtained by using the theory of viscoelastic-plastic mechanics and damage mechanics. An improved Zienkiewicz–Pande parabola-type yield criterion was used instead of a linear Newton body to obtain a coupled constitutive model of viscoelastic-plastic damage in the frozen soil under the unloading stress paths and to derive the coupling flexibility matrix for viscoelastic and viscoplastic damage. A finite element program of artificial frozen soil considering creep damage was written in the Visual Fortran 6.6A environment and embedded into the nonlinear finite element software ADINA as a user subroutine. The results of numerical simulation and laboratory testing were identical, with a maximum error of no more than 4.8%. This work shows that it is reasonable to describe the creep constitutive model of frozen soil with the viscoelastic-plastic-coupled constitutive model.